A criterion of exponential dichotomy for a countable system of differential equations with quasiperiodic coefficients - Elnazarov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We establish necesary and sufficient conditions for the exponential diehetemy with matrix projeseters of a countable system of differential equations with quasiperiodic coefficients.